Page 517 - Álgebra
P. 517

tog3 x-y[y= log3 x +log3 <¡y





                     —> log3x+  log3y   2  = iog3x-r --Ica- y




                         i x 3y 4  1
                     log         = l°g (x3-y4)-   logz'




                     —> logx^ -flogyT-6togz=3!ogx-r 4!ogy-6icgz


                                                                                     *   Logaritm o  com ún
              3.  Combinamos ¡as expresiones en un solo logaritmo.



                  •   31ogx  + —iog(x + 1)  =Iogx3r-log(x-f-1)2                         Ejemplos

                                                                                        -  !og105 = !cg5
                                                                                        -  -¡og,017=!cgl7
                      —> log*3 T!og7x+1=logx3-vx-rl

                                                                                        Logaritm o  naturai
                      Iog35 + 5iog32



                      -e»  log35 + log32^=iog35-rlog332                                  conde  e  es  el  nùmero  ce
                                                                                         Euler.
                                                                                         e=2,718281...
                      —7  log35-32=log3160
                                                                                         Ejemplos
                                           N                                             -  !n 5 = lo g .5
                      log2^ + log2S-2log2C
                                                                                         -  in20=!cg.20

                                                                                     *   Además
                           Iog2/A-S-log2C^=log2 ^
                                                                                         In1=0
                                                                                         ine=1
                                                                                         Ine^x
                      log12 + Ìo g 7 -lo g 2  = log12 + log72 -log2



                           log 12 + log V7 - log 2 = log 12 ••// - log 2





                      —»  log     ^ = log 6>/7
   512   513   514   515   516   517   518   519   520   521   522